Parindo a nação? maternidades, amamentação e o discurso médico higienista na corte imperial (Rio de Janeiro, décadas de 1870 e 1880) - Santos, Nubia Sotini dos (2023)
This dissertation analyzes hygienist medical discourses on maternity, breastfeeding practices and infant care, aiming to understand their association with a national project. The documentary sources are the medical theses of the Medical School of Rio de Janeiro during the 1870s and 1880s, a period when the ideals of progress and European civility reached the Brazilian capital and the country. In that context, motherhood and breastfeeding became central subjects in a deep and intense political debate. The analysis of the medical theses demonstrates the formation of a playing field, which condemns breastfeeding by wet nurses–mostly enslaved–, called “mercenary breastfeeding”, and advocates breastfeeding by the biological mother, called “maternal breastfeeding”. From these debates, doctors aimed to build a physically and morally healthy nation that could distance itself from the colonial perspective in transition at the end of the empire. To raise the modernity and civilization of Brazilian nation, white mothers were encouraged to breastfeed, thus becoming salvationists. By breastfeeding their own children, they guaranteed the kids survival, as well as the protection of the nation. Doctors understood mercenary breastfeeding, on the other hand, as harmful for both children–who could become ill through an alleged contagion through milk—and the homeland progress. Through content analysis, as well as discourse and silence analysis, we examine how, during the final decades of the 19th century, doctors represented the presence and the absence of white mothers, also the role of wet nurses. We consider the absence of the enslaved maternal figure in doctors’ writings too. The concept of necrobiopoder (necro-biopower) works to demonstrate how the medical discourses of that time were committed to the survival of white children, thought of as the future of the nation, as well as neglected the lives of black children born to enslaved mothers.